2013
DOI: 10.1027/1618-3169/a000216
|View full text |Cite
|
Sign up to set email alerts
|

Different Response Patterns Between Auditory Spectral and Spatial Temporal Order Judgment (TOJ)

Abstract: Temporal order judgment (TOJ) thresholds have been widely reported as valid estimates of the temporal disparity necessary for correctly identifying the order of two stimuli. Data for two auditory TOJ paradigms are often reported in the literature: (1) spatially-based TOJ in which the order of presentation of the same stimulus to the right and left ear differs; and (2) spectrally-based TOJ in which the order of two stimuli differing in frequency is presented to one ear or to both ears simultaneously. Since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(51 citation statements)
references
References 56 publications
(114 reference statements)
2
49
0
Order By: Relevance
“…However, performance in the spectral task improved significantly between sessions, raising the question as to what specifically participants learn while performing it. Previously, when comparing spectral TOJ with spatial TOJ, it was suggested that while performing the spectral TOJ task, participants learn to use the frequency difference between the tones as a cue for determining the order of the tones [1]. This cue enables the listener to create a global pattern for each sequence (high-low vs. low-high) and to report the order of the tones by differentiating between patterns rather than by attending to each of the tones in the sequence.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, performance in the spectral task improved significantly between sessions, raising the question as to what specifically participants learn while performing it. Previously, when comparing spectral TOJ with spatial TOJ, it was suggested that while performing the spectral TOJ task, participants learn to use the frequency difference between the tones as a cue for determining the order of the tones [1]. This cue enables the listener to create a global pattern for each sequence (high-low vs. low-high) and to report the order of the tones by differentiating between patterns rather than by attending to each of the tones in the sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The practice session included 30 pairs of stimuli that were presented with an ISI of 250 ms (see also [1]). …”
Section: Spectral Tojmentioning
confidence: 99%
See 3 more Smart Citations